2017
DOI: 10.1016/j.tem.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids and Lipoproteins in Health and Metabolic Disorders

Abstract: Sphingolipids are structurally and functionally diverse molecules with significant physiologic functions and are found associated with cellular membranes and plasma lipoproteins. The cellular and plasma concentrations of sphingolipids are altered in several metabolic disorders and may serve as prognostic and diagnostic markers. Here, we discuss different sphingolipid transport mechanisms and highlight how changes in cellular and plasma sphingolipids levels contribute to cardiovascular disease, obesity, diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(176 citation statements)
references
References 86 publications
5
167
2
2
Order By: Relevance
“…It is becoming clear that plasma sphingolipids could be markers for several metabolic disorders such as insulin resistance, progression of NAFLD to NASH, atherosclerosis, and coronary artery disease (6)(7)(8)(9)(10)(11)(12)(13). However, very little is known about the mechanisms that control plasma sphingolipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming clear that plasma sphingolipids could be markers for several metabolic disorders such as insulin resistance, progression of NAFLD to NASH, atherosclerosis, and coronary artery disease (6)(7)(8)(9)(10)(11)(12)(13). However, very little is known about the mechanisms that control plasma sphingolipids.…”
Section: Discussionmentioning
confidence: 99%
“…A published study showed significantly reduced sphinogsine-1P levels in the plasma of older Tangier subjects with very low levels of HDL and apoAI (99% and 97% reduction, respectively) (43). It is known that sphinogsine-1P transport to plasma involves apoM and spinster 2 and resides mainly on HDL 3 (6,(44)(45)(46). Longitudinal, prospective studies in larger cohorts are needed to determine plasma apoM, sphingoid bases, and their phosphate levels in Tangier subjects.…”
Section: Sphingoid Bases and Their Phosphatesmentioning
confidence: 99%
“…Ståhlman et al found that small HDL-particles predominated in dyslipidemic subjects, with and without diabetes, compared to respective normolipidemic controls, and were distinguished as the primary carrier of ceramides, which is known for promoting inflammation and insulin resistance [16]. In healthy individuals, LDL particles are typically the major carriers of ceramide compared to VLDL and HDL particles [33,42]. In the current study, when lipoprotein particles were incubated in vitro with different ceramide species, C16 ceramide had the highest level of incorporation into all lipoproteins (LDL, HDL2, HDL3) ( Figure 2).…”
Section: Ceramide Enrichment Of Lipoprotein Particlesmentioning
confidence: 99%
“…С возрастом снижается продукция липидов кожи, но соотношение не меняется [12]. При различных метаболических нарушениях концентрация липидов кожи, а также церамидов крови может служить прогностическим и диагностическим маркерами сердечно-сосудистых заболеваний, ожирения, сахарного диабета, инсулинорезистентности и неалкогольной жировой болезни печени [13][14][15][16].…”
Section: характеристика липидного состава при заболеванияхunclassified